Hubungan Dukungan Keluarga dengan Kepatuhan Berobat Penderita Tuberkulosis di Kabupaten Bolaang Mongondow Timur - Siska Sibua; Grace Irene Viodyta Watung (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
Indonesia still has a big problem in dealing with TB disease. The purpose of this study is to find out the Relationship between Family Support with Tuberculosis Treatment Compliance in east Bolaang Mongodow Regency. This research method uses this type of quantitative research. This study is an analytical observational study with the design used, it is called cross sectional study. Research has been conducted in East Bolaang Mongondow Regency from April 2021 to June 2021. The population in this study was 130 respondents. Based on the results of cross-tabulation between free variables (Family support) and bound variables (Adherence to tuberculosis patients) using chi square statistical tests obtained a value of p value = 0,000 so that it can be concluded there is a Family Support Relationship with tuberculosis treatment compliance in East Bolaang Mongodow Regency. It is expected to the East Mongodow District Health Office to be able to cooperate with the family in maximizing the role of the family in the treatment process of family members.